4 - L’État face au phénomène de la migration irrégulière vers l’Europe : à la recherche de la souveraineté migratoire du Sénégal - Agne, Malado (African Sociological Review, 2023)
This paper analyses the phenomenon of illegal migration towards Europe from Senegal within the context of a global regulation of international migration. The paper questions more specifically the place and the position of Senegal, as a country that people leave or go to, in complex international, inter-regional and inter-State relations which govern migrations. The analysis shows that a massive and large-scale use of foreign legal framework, policies, financial and material resources, lead to the atrophy of the political power of the Senegalese State regarding migration matters, in contradiction with key aspects of the principle of sovereignty.